Changes in demographic components during the COVID-19 pandemic and economic recession in Sri Lanka - De Silva, W. Indralal; De Silva, Ranjith; Kumarasinghe, Malith (National Science Foundation, Colombo, 2024)
The objective of this paper is to investigate the impact of the COVID-19 pandemic and subsequent economic recession on the three demographic components, namely mortality, fertility and migration in Sri Lanka and possible implications. A secondary data analysis of mortality, fertility, migration, and marriage data from the Registrar General’s Department of Sri Lanka and the Ministry of Health was conducted. Although excess mortality (COVID-19 deaths) in 2022 was substantially lower, it was elevated in 2021. In comparison to non-COVID-19 years, the number of deaths has increased substantially during the post-COVID-19 era – 146 thousand deaths in 2019 increased to 194 thousand in 2023 (30.1%). This marked increase could be attributed to the economic recession and related serious constraints faced by the health system in Sri Lanka. Further, a marked decrease in marriages (14.2%) was observed in 2020 due to COVID-19 which recovered to pre-COVID-19 level in 2021. However, instead of experiencing the “babyboom” phenomenon (as observed in some previous pandemics) in the aftermath of the COVID-19 pandemic, the observed data for Sri Lanka indicates a significant downward trend in fertility. Unexpectedly, 319 thousand births were reported in 2019 in Sri Lanka dropping to 257 thousand by 2023, which is a decline of over 62 thousand births (19%). This situation is further complicated by the highest reported outbound migration ever reported in Sri Lanka in 2022, displaying a 250% year-toyear increase. The changes in these demographic components would impact the macroeconomics and the future size of the Sri Lankan population.
Keywords: The COVID-19 pandemic; Mortality; Fertility; Marriage; Economic recession